2020
DOI: 10.1186/s13047-020-00389-w
|View full text |Cite
|
Sign up to set email alerts
|

The ankle brachial index in people with and without diabetes: intra‐tester reliability

Abstract: Background: The ankle-brachial index (ABI) is widely used for determining the presence and severity of peripheral arterial disease (PAD), and current guidelines suggest it should be used to monitor possible progression in affected individuals. It is therefore important that the technique demonstrates adequate reliability for repeated measurements. Existing studies suggest that the ABI is reliable in the general population however, there is a lack of evidence for the reliability of the ABI in people with diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…The main drawback is that ABI cannot accurately locate the vascular lesion and is unable to determine the morphological changes in vessels. Its sensitivity will also be significantly reduced when patients suffer from diseases involving small vessels, such as diabetes because such diseases are more likely to co-exist with medial arterial calcification which can prevent compression and pressure measurement [ 28 , 29 ]. Therefore, a normal ABI does not exclude the presence of PAD [ 27 ].…”
Section: Early Screening Methods For Pad In Icvd Patientsmentioning
confidence: 99%
“…The main drawback is that ABI cannot accurately locate the vascular lesion and is unable to determine the morphological changes in vessels. Its sensitivity will also be significantly reduced when patients suffer from diseases involving small vessels, such as diabetes because such diseases are more likely to co-exist with medial arterial calcification which can prevent compression and pressure measurement [ 28 , 29 ]. Therefore, a normal ABI does not exclude the presence of PAD [ 27 ].…”
Section: Early Screening Methods For Pad In Icvd Patientsmentioning
confidence: 99%
“…For ankle systolic pressure, the higher pressures of the dorsal pedis artery and posterior tibial artery were used. The Doppler method measuring ABI has gained reliability in previous studies [ 11 , 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…79 No studies included people with DFU. Two studies reported participants having diabetes-related complications including neuropathy, nephropathy, retinopathy 74,75 and one study reported previous history of vascular surgery (36.7%), intermittent claudication symptoms (36.7%), rest pain symptoms (3.3%). 77 CHUTER ET AL.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…There was little consistency in the training and qualifications of the raters. The tests were performed using students, 77 inexperienced and experienced podiatrists, 75,78 diabetes educator, vascular sonographer, 76 and vascular technologists. 79 The majority of studies used manual methods for performing the measurements with 1 study reporting the use of automated devices.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%